An exploratory study : the family's experience of the initial interview at the Child Guidance Clinic - Naicker, Allengary (Department of Psychology, 2014)
This project was an evaluation of the initial interview as experienced by a sample of six families who utilised the services of the CGC in 2003. Families were given a semi-structured interview schedule which focussed on a number of common experiences of the assessment interview. A thematic analysis was employed to understand this qualitative enquiry into the family's perception of a service sometimes criticised as traditional, elitist and contradictory to the proposal that a broader, more community based intervention be proffered.